A rational policy decision or political deal? A multiple streams' examination of the Russia-China natural gas pipeline. (January 2021) - Liu, Dawei; Xu, Hang
Abstract: After more than twenty years of waiting, the first gas pipeline connecting Russia and China—the Power of Siberia—began transporting gas in December 2019. Although much has been discussed concerning disputes over pricing and the route of this pipeline, the relevant events inside each nation, e.g. China's energy mix transition, its gas pricing reform, the reshuffle of Russia's natural gas industry, etc., that helped catalyze the deal have yet to be fleshed out. This paper analyzes the decision-making behind the deal using the multiple streams framework (MSF) which is well suited for the examination of decision-making under circumstances of ambiguity. Our analysis demonstrates the ambiguous policymaking circumstances for the gas deal and reveals how policy disputes over price and routing paralleled and interacted with the changing political landscapes and shifting problem agendas in both nations before they were coupled together by political leaders in 2014. The insights derived here are also helpful in analyzing other cross-border pipeline deals. Highlights: Presentation of a multiple streams analysis of the 2014 Russia-China gas deal. Domestic energy situations in both nations catalyzed this deal. A set of domestic factors leading to POS was specified. The policymaking circumstances for the deal was ambiguous. Both sides made concessions in the 2014 deal.